Impaired HSP70 Expression in the Aorta of Female Rats: A Novel Insight Into Sex-Specific Differences in Vascular Function - de Oliveira, Amanda Almeida; Priviero, Fernanda; Webb, R. Clinton; Nunes, Kenia Pedrosa (Frontiers in Physiology, 2021)
Heat-shock protein 70 (HSP70) contributes to cellular calcium (Ca2+) handling mechanisms during receptor-mediated vascular contraction. Interestingly, previous studies have independently reported sex-related differences in HSP70 expression and Ca2+ dynamics. Still, it is unknown if sex, as a variable, plays a role in the impact that HSP70 has upon vascular contraction. To narrow this gap, we investigated if differences exist in the expression levels of HSP70 in the aorta, and if targeting this protein contributes to sex disparity in vascular responses. We report that, compared with male animals, female rats present a reduction in the basal levels of HSP70. More compelling, we found that the blockade of HSP70 has a greater impact on phenylephrine-induced phasic and tonic vascular contraction in female animals. In fact, it seems that the inhibition of HSP70 significantly affects vascular Ca2+ handling mechanisms in females, which could be associated with the fact that these animals have impaired HSP70 expression. Corroborating this idea, we uncovered that the higher sensitivity of female rats to HSP70 inhibition does not involve an increase in NO-dependent vasodilation nor a decrease in vascular oxidative stress. In summary, our findings reveal a novel mechanism associated with sex-specific differences in vascular responses to α-1 adrenergic stimulation, which might contribute to unraveling the network of intertwined pathways conferring female protection to (cardio)vascular diseases.